KOMUNIKASI NEWSPAGE UNTUK PENINGKATAN PENJUALAN PADA PERUSAHAAN PANGAN - Utomo, Seto Setiawan Wisnu (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
Sales Division is the spearhead of a company because the sales division is directly dealing with consumers with the aim of generating corporate profits. This study analyzes the impact of using the Newspage DMSOne system on increasing company sales in terms of sales force effectiveness and the effectiveness of promotional activities. Using a quantitative approach, the sample and object of this research are the activities of visits (hits) and promotion of salespeople who use Handheld Terminals (HHT), in this case, the intended salespeople are traditional-type salespeople - General Trade (GT), modern-Modern Trade (MT), and Wholesalers (WS). Because salespeople with this type feel directly the use of the DMSOne system through the Handheld Terminal (HHT). The results show that communication through DMSOne Newspage has a positive influence on GT traditional salespeople. Regression results show that with this new communication system, the number of visits and total promos has a positive effect on sales by 72.3%, which means it is strong enough to describe the things that affect sales.